2019
DOI: 10.15789/1563-0625-2019-3-407-418
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Essential Hypertension

Abstract: According to modern concept of the etiopathogenesis of essential hypertension, immune cells play an important role in its development. Mediators produced by immunocompetent cells participate in the initiation and maintenance of chronic systemic inflammation and promote the development of vascular remodeling which is an important part of the pathogenesis of the disease and target organ damage. The immune mechanisms underlying blood pressure elevation include the activation of innate and adaptive immune cells. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
3
0
3
Order By: Relevance
“…Так, при гипертрофии миокарда левого желудочка и при бессимптомном атеросклерозе сосудов снижается фагоцитарная активность нейтрофилов периферической крови и повышается их кислород-зависимая активность, тогда как при хронической болезни почек фагоцитарная активность нейтрофилов не изменена. Повышение показателей НСТ-теста, наблюдаемое во всех изученных группах больных артериальной гипертонией, отражает генерацию активных форм кислорода, что приводит к развитию «окислительного стресса» в тканях органа-мишени: сосуды -атеросклеротическое поражение, почки -развитие хронической болезни почек, сердце -гипертрофия миокарда [17].…”
Section: Discussionunclassified
“…Так, при гипертрофии миокарда левого желудочка и при бессимптомном атеросклерозе сосудов снижается фагоцитарная активность нейтрофилов периферической крови и повышается их кислород-зависимая активность, тогда как при хронической болезни почек фагоцитарная активность нейтрофилов не изменена. Повышение показателей НСТ-теста, наблюдаемое во всех изученных группах больных артериальной гипертонией, отражает генерацию активных форм кислорода, что приводит к развитию «окислительного стресса» в тканях органа-мишени: сосуды -атеросклеротическое поражение, почки -развитие хронической болезни почек, сердце -гипертрофия миокарда [17].…”
Section: Discussionunclassified
“…Previously, it was shown that level of fibrinogen, C-reactive protein (CRP) and neopterin was increased in inflammatory events, which serve as sensitive markers for inflammation and necrosis. Their rise in the serum higher than reference values correlates with increased risk of complications in cardiovascular diseases [9,10].…”
Section: Introductionmentioning
confidence: 92%
“…Th1-подтип лимфоцитов генерирует выработку TNFα, IL-2, IFNγ; Th2-подтип продуцирует IL-4, IL-5, IL-10, IL-13, ингибирует клеточно-опосредованный иммунитет и стимулирует В-лимфоциты. [27,40].…”
Section: Introductionunclassified